Endogenous ouabain and aldosterone are coelevated in the circulation of patients with essential hypertension. Issue 10 (October 2016) - Tentori, Stefano; Messaggio, Elisabetta; Brioni, Elena; Casamassima, Nunzia; Simonini, Marco; Zagato, Laura; Hamlyn, John M.; Manunta, Paolo; Lanzani, Chiara
Abstract : Objective: In the setting of normal sodium (Na) intake, many patients with hypertension have inappropriately elevated plasma aldosterone (Aldo) levels and may be at increased risk for tissue damage. Moreover, other adrenocortical steroids, including endogenous ouabain can stimulate tissue damage. As endogenous ouabain is often elevated in chronically Na-loaded states, is a vasoconstrictor, raises blood pressure (BP), and also promotes tissue fibrosis, we investigated the extent to which plasma Aldo and endogenous ouabain were coelevated among naïve hypertensive patients (NHP). We also investigated the impact of an acute salt load on these steroids, BP, and renal function. Methods: NHP (590) were grouped in tertiles based on their baseline plasma Aldo (mean ± SEM first 7.59 ± 0.18, versus third 24.15 ± 0.31 ng/dl). Baseline plasma renin activity (2.4 ± 0.1 versus 1.2 ± 0.1 ng/ml per h, P  < 0.001), endogenous ouabain (268 ± 14.9 pmol/l versus 239.0 ± 13.6 pmol, P  < 0.01) and DBP (91.9 ± 0.76 versus 89.6 ± 0.71 mmHg, P  = 0.017) were higher in NHP in the third versus the first Aldo tertile, respectively. Results: Acute Na loading showed that the BP of the third Aldo tertile NHP was especially salt-sensitive (slope of pressure–natriuresis relationship 0.015 ± 0.002 versus 0.003 ± 0.001 μEq/mmHg per min, P  = 0.00024 after adjustment for sex, BMI, and age). Regression analyses showed that plasma Aldo and endogenous ouabain were linearly related (β = 0.181, P  = 0.0003). Conclusion: Among patients with essential hypertension, circulating endogenous ouabain and Aldo are typically coelevated and their BP is salt-sensitive. In conditions where Aldo is inappropriately elevated, both Aldo and endogenous ouabain may contribute to adverse cardiovascular and renal outcomes.